(untitled) (Research, Society and Development, 2021)
When one thinks about the natural course of life, one imagines that the human being is born, grows, grows old and only then goes through the process of death. In a neonatal and pediatric intensive care unit - Neopediatric ICU, the course of life can be shortened, and the end of life can become a real fact for the newborn/child. When analyzing the actions taken towards the patient, in the case of nursing, the palliative approach follows a macro line of care, restricted to compliance with medical prescriptions and carrying out procedures. Given the importance of the palliative care approach, we raise the following question: What are the strategies used by physicians and nurses in the eligibility and palliative care of patients hospitalized in a neopediatric ICU, and their families? The articles were selected and organized following the PICO strategy. After delimiting the available literature, a careful analysis was carried out so that the most relevant topics in the articles could be organized. Several obstacles directly affect care, such as training, complexity of procedures, lack of privacy with patients and family members, professional unpreparedness, among others. Finally, it is concluded that the literature review managed to gather a consistent and very useful content, contributing to the enrichment of knowledge about Palliative Care and how medical and nursing professionals are able to approach palliative care in the neonatal ICU, always seeking to offer the best assistance to their patients and families despite all the challenges encountered in the routine of the service.